Piperlongumine conjugates induce targeted protein degradation. Issue 2 (16th February 2023) - Pei, Jing; Xiao, Yufeng; Liu, Xingui; Hu, Wanyi; Sobh, Amin; Yuan, Yaxia; Zhou, Shuo; Hua, Nan; Mackintosh, Samuel G.; Zhang, Xuan; Basso, Kari B.; Kamat, Manasi; et al.
Summary: Proteolysis targeting chimeras (PROTACs) are bifunctional molecules that degrade target proteins through recruiting E3 ligases. However, their application is limited in part because few E3 ligases can be recruited by known E3 ligase ligands. In this study, we identified piperlongumine (PL), a natural product, as a covalent E3 ligase recruiter, which induces CDK9 degradation when it is conjugated with SNS-032, a CDK9 inhibitor. The lead conjugate 955 can potently degrade CDK9 in a ubiquitin-proteasome-dependent manner and is much more potent than SNS-032 against various tumor cells in vitro . Mechanistically, we identified KEAP1 as the E3 ligase recruited by 955 to degrade CDK9 through a TurboID-based proteomics study, which was further confirmed by KEAP1 knockout and the nanoBRET ternary complex formation assay. In addition, PL-ceritinib conjugate can degrade EML4-ALK fusion oncoprotein, suggesting that PL may have a broader application as a covalent E3 ligase ligand in targeted protein degradation. Graphical abstract: Highlights: PL-SNS-032 conjugate 955 potently degrades CDK9 in a CRL E3 ligase-dependent manner TurboID-bait assay identifies KEAP1 as the E3 ligase recruited by 955 955 recruits KEAP1 via covalent binding 955 is a more potent anti-cancer agent than SNS-032 Abstract : Pei et al. identify piperlongumine (PL), a natural product, as a new covalent E3 ligase ligand to generate bivalent protein degraders. Using a proximity labeling assay KEAP1 was identified as the E3 ligase recruited by PL to potently degrade CDK9 when PL was conjugated with the CDK9 inhibitor SNS-032.